Justice and mental health: understanding the insanity defense in Malaysia - Kamarudin, Irma; Che Rose, Sarirah; Abdullah Sanek, Siti Khadijah (Universiti Teknologi MARA, Kedah, 2025)
Defense of insanity refers to a defense that can be raised by an accused who was insane at the time of the crime. All modern legal systems have a version of the defense of insanity, and Malaysia is no exception. This dialogue begins by addressing the historical development of the defense of insanity, then followed by a discussion on the theoretical underpinnings of such defense that seeks to draw a distinction between treatment and punishment, illness and evil, and misfortune and culpability. The aim is to educate readers about the medical, cultural, and social contexts of mental disorders. In so doing, it is hoped that the lawfulness and ethicality of a non-insane person receiving treatment will be clear.